Analisi costo/efficacia della doxofillina vs. teofillina nella terapia dell’asma cronica reversibile dell’adulto - Eandi, Mario; Berno, Elisa; Pradelli, Lorenzo (Farmeconomia. Health economics and therapeutic pathways, 2002)
Doxofylline is a methyl-xanthine with bronchodilator activity which clinical efficacy in the treatment of asthma and COPD is equivalent to theophylline. Clinical trials prooved that while doxofylline is as effective as theophylline in the treatment of asthma, it is associated with lesser side effects. For our pharmacoeconomical evaluation, we employed the data of an international multi-centric study that compared the efficacy and tolerability of 12 weeks of treatment with either theophylline 250 mg tid, or doxofylline 400 mg tid, or placebo. The efficacy was evaluated with pulmonary function tests and by recording the number of asthma attacks and beta-2 agonist puffs: doxofylline 1200 mg/day and theophylline 750 mg/day resulted equally effective, but the former resulted better tolerated, as the adverse effects were lesser in number and severity. We performed a cost/effectiveness analysis in order to compare the two treatments, considering the perspective of the Italian health system (SSN) and of the Italian society. For the purposes of this analysis, the efficacy indices we considered were two: one simple, consisting in the number of avoided asthma attacks (AAA), and a more complex one, i.e. UATD (Utility Adjusted Therapy Days). For the construction of this index, we extracted the survival curve of the patients remaining in therapy; this curve showed that the cumulative number of therapy days is significantly greater in the doxofylline group, although the percentage of dropouts is similar at the end of the three months: this is due to the fact that the drop-outs in the theophylline group occur earlier after treatment start. The number of therapy days was then weighed for an utility index inversely proportional to the main daily number of avoided asthma attacks, thus obtaining the UATDs. The results of the cost/effectiveness analyses showed that doxofylline dominates theophylline treatment in asthma, as it is less expensive and more effective (in terms of AAAs and UATDs) for both considered decision-makers, i.e. Italian SSN and society. The consistency of these results was further confirmed by oneway sensitivity analyses.